Wine consumption and sales strategies: The evolution of Mass Retail Trading in Italy - Maria Moneti; Caterina Romano; Gabriele Scozzafava; Fabio Boncinelli; Leonardo Casini (Wine Economics and Policy, 2015)
The recent economic crisis has brought considerable changes also to food consumption: on one hand, many products have recorded consistent absolute declines in demand, while on the other hand, we have witnessed preferences shift towards low-cost foods or, in any event, foods of lower quality standards. In order to study these phenomena and, especially, the strategies firms adopt to confront them, the wine sector constitutes a particularly interesting focus due to its wide supply range and the elevated reactivity to price and income of demand. Our paper intends to take a close look at wine consumptions, focusing on the sales made on the Mass Retail Trading (MRT) channel from 2009 to 2013, and to conduct a thorough analysis of the performances of the single products, in view of pointing out the sector's overall trend, as well as the principal typologies of wine, in terms of their sales results in that period. Applying Latent Class Regression has permitted us to identify six explicative models of performances, demonstrating the effect on sales of the structural characteristics of productions and sales strategies.
Keywords: 330; Latent Class Regression; Sale strategies; Wine